1982
DOI: 10.1002/lipi.19820840903
|View full text |Cite
|
Sign up to set email alerts
|

Complex‐Formation between Glucosinolates and Tetrachloropalladate(II) and its Utilization in Plant Breeding

Abstract: A method is described which allows a fast determination of the content of glucosinolates in cruciferous seeds. Basically the reaction between glucosinolates and tetrachloropalladate (II) is used. For the quantitative measurement of the resulting coordination complexes an 8‐channel photometer is recommended. Furthermore an analytical grist‐mill has been constructed which allows a fast preparation of the samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 3 publications
0
36
0
Order By: Relevance
“…The use of myrosinase is avoided in the method described by BRZEZINSKI et al [4] in which glucosinolates are hydrolysed with sulphuric acid and the released glucose is measured colorimetrically after reaction with thymol. MOLLER et al [25] have described an ion exchange clean-up procedure which when applied to the palladium glucosinolate complexing method first reported by THIES [38], results in a more specific test. SMITH et al [36] concluded that the carefully controlled use of a glucose test tape procedure provided an adequate means for screening breeder's lines.…”
Section: Recommended Methods For Glucosinolate Analysismentioning
confidence: 99%
“…The use of myrosinase is avoided in the method described by BRZEZINSKI et al [4] in which glucosinolates are hydrolysed with sulphuric acid and the released glucose is measured colorimetrically after reaction with thymol. MOLLER et al [25] have described an ion exchange clean-up procedure which when applied to the palladium glucosinolate complexing method first reported by THIES [38], results in a more specific test. SMITH et al [36] concluded that the carefully controlled use of a glucose test tape procedure provided an adequate means for screening breeder's lines.…”
Section: Recommended Methods For Glucosinolate Analysismentioning
confidence: 99%
“…To determine amino acids, samples were hydrolyzed with 6 M HCl at 110 for 24 h, and the amino acid composition of hydrolysates was analyzed by HPLC (Hitachi L-8900 Amino Acid Analyzer, Tokyo, Japan). The content of glucosinolate, erucic acid and tannin was determined by the palladium chloride (Thies, 1982), measuring iron pectmphotometric (Latta and Eskin, 1980), and Folin-Denis (Folin and Denis, 1912) methods, respectively.…”
Section: Sampling and Biochemical Analysesmentioning
confidence: 99%
“…The seed samples for the analysis of glucosinolates, fiber and sinapine concentration were collected from ten self-pollinated plants from each tested line. Glucosinolates and fiber content was determined by nearinfrared reflectance spectroscopy (NIRS) (Thies, 1982, Biston et al, 1988, Velasco et al, 1999. These analyses were performed at the Małyszyn Laboratory that belongs to Plant Breeding Strzelce.…”
Section: Methodsmentioning
confidence: 99%